2022
DOI: 10.12659/msm.937949
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Orthodontic Mini-Implant Placement in the Maxillary Anterior Alveolar Region in 15 Patients by Cone Beam Computed Tomography at a Single Center in South India

Abstract: Background In this study, we aimed to evaluate orthodontic mini-implant placement in the maxillary anterior alveolar region by cone beam computed tomography (CBCT) in 15 patients at a single center in South India. Material/Methods A total of 15 CBCT scans of orthodontic patients after completion of leveling and aligning stage were included. The thickness of labial alveolar bone, labio-palatal bone, and inter-radicular distance between the maxillary central incisors (U1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…9,10 For instance, Smith et al found that class II disorder generally tend to exhibit narrower inter-radicular areas, in particular within the maxilla, which is consistent with our observations. [11][12][13] Conversely, class III disorder frequently showed wider bone dimensions at the apical stage, corresponding to similar findings by Johnson et al 14 This concurrence emphasizes the significance of considering growth styles when planning orthodontic remedies, specifically those involving miniscrew implants, to make sure the safe and effective placement of those gadgets.…”
Section: Growth Pattern Influence On Inter-radicular Bone Dimensionssupporting
confidence: 77%
“…9,10 For instance, Smith et al found that class II disorder generally tend to exhibit narrower inter-radicular areas, in particular within the maxilla, which is consistent with our observations. [11][12][13] Conversely, class III disorder frequently showed wider bone dimensions at the apical stage, corresponding to similar findings by Johnson et al 14 This concurrence emphasizes the significance of considering growth styles when planning orthodontic remedies, specifically those involving miniscrew implants, to make sure the safe and effective placement of those gadgets.…”
Section: Growth Pattern Influence On Inter-radicular Bone Dimensionssupporting
confidence: 77%
“…According to Yu Murugesan et al , CBCT can be utilized to assess the placement of orthodontic mini-implants in the maxillary anterior alveolar area. [ 2 ]…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, in most patients, only the apical portion of the dental roots is present in the ANS region. Therefore, the apical inter-radicular space between these roots is larger than that between the middle part, rendering it more likely to accommodate mini-implants [35,36] without damaging the roots.…”
Section: Discussionmentioning
confidence: 99%